Interactive and Immersive Practices; Critical Spatial Practices. The Augmented Reality of the Exhibition Space Pratiques interactives et immersives ; pratiques spatiales critiques. La réalité augmentée de l’espace d’exposition - Alessandra Mariani (MediaTropes, 2012)
The rise of installations, as well as immersive and interactive spaces, in both art and science museums has accustomed the public to heightened interactivity, leading to a better understanding of social, natural and scientific phenomena. These spatial systems have also paved the way for the production of innovative environments within exhibition design. This article aims to present a brief overview of the origins of immersive and sensory practices at work in contemporary museums, and to evaluate the potential of these processes to generate critical thinking in the visitor. A concise description of the evolution of the operational and intellectual premise of these museums and their changing practices demonstrates the transformations that have occurred, their modalities, and their application in selected works, notably: The Weather Project by Olafur Eliasson presented at Tate Modern London; Diller + Scofidio’s media pavilion, Blur Building, in Yverdon-les-Bains in Switzerland; and the exhibition Sense of the City at the Canadian Centre for Architecture in Montreal. La multiplication d’installations, d’espaces immersifs et interactifs dans les musées d’art et ensuite dans les musées de sciences, a accoutumé le public à interactivité augmentée favorisant la compréhension de phénomènes sociaux, naturels ou scientifiques. Ces systèmes spatiaux ont ainsi frayé la voie au développement de techniques de scénarisation environnementales. L’article vise à présenter succinctement les origines des pratiques immersives et sensorielles à l’œuvre dans l’espace muséal contemporain et à présenter le potentiel de ces processus à engendrer une réflexion, un raisonnement critique chez le visiteur. Une courte description de l’évolution des postures opérationnelles et intellectuelles du musée et de ces pratiques permettra d’en retracer la transformation, les modalités et l’application dans des œuvres, notamment l’installation The Weather Project par Olafur Eliasson présentée au Tate Modern à Londres, le pavillon médiatique de Diller + Scofidio Blur Building à Yverdon-les-Bains en Suisse et l’exposition Sensations urbaines présentée au Centre Canadien d’Architecture à Montréal.